(untitled) (American Journal of Engineering , Mechanics and Architecture (2993-2637), 2025)
This article is about simulation of all the type of FM and AM with full control over every aspect of this two modulation including there amplitude modulation index and many more and show the difference between the AM type like double side band transmitted carrier and double sideband suppressed carrier and single side band suppressed carrier and show briefed compression between MATLAB Simulink with LabView and why should choose the LabView in the comminution simulation also studying spectral analyzer which can be used to measure frequency spectrum and the simulation that we done it include in Realtime modulation and FFT (Fast Fourier Transform ) that used to show the signal in frequency domain , also we can mention that the simulation in this project contain wide range of excrement which mean it not limited for range of input value.